Are general surgery residents adequately prepared for hepatopancreatobiliary fellowships? A questionnaire‐based study. Issue 3 (11th November 2014) - Osman, Houssam; Parikh, Janak; Patel, Shirali; Jeyarajah, D. Rohan
Abstract Background The present study was conducted to assess the preparedness of hepatopancreatobiliary (HPB) fellows upon entering fellowship, identify challenges encountered by HPB fellows during the initial part of their HPB training, and identify potential solutions to these challenges that can be applied during residency training. Methods A questionnaire was distributed to all HPB fellows in accredited HPB fellowship programmes in two consecutive academic years (n = 42). Reponses were then analysed. Results A total of 19 (45%) fellows responded. Prior to their fellowship, 10 (53%) were in surgical residency and the rest were in other surgical fellowships or surgical practice. Thirteen (68%) were graduates of university‐based residency programmes. All fellows felt comfortable in performing basic laparoscopic procedures independently at the completion of residency and less comfortable in performing advanced laparoscopy. Eight (42%) fellows cited a combination of inadequate case volume and lack of autonomy during residency as the reasons for this lack of comfort. Thirteen (68%) identified inadequate preoperative workup and management as their biggest fear upon entering practice after general surgery training. A total of 17 (89%) fellows felt they were adequately prepared to enter HPB fellowship. Extra rotations in transplant, vascular or minimally invasive surgery were believed to be most helpful in preparing general surgery residents pursing HPB fellowships. Conclusions Overall, HPB fellows felt themselves to be adequately prepared for fellowship. Advanced laparoscopic procedures and the perioperative management of complex patients are two of the challenges facing HPB fellows. General surgery residents who plan to pursue an HPB fellowship may benefit from spending extra rotations on certain subspecialties. Focus on perioperative workup and management should be an integral part of residency and fellowship training.